No Impact of Deep Brain Stimulation on Fear-Potentiated Startle in Obsessive–Compulsive Disorder - Baas, Johanna M. P.; Klumpers, Floris; Mantione, Mariska H.; Figee, Martijn; Vulink, Nienke C.; Schuurman, P. Richard; Mazaheri, Ali; Denys, Damiaan (Frontiers in Behavioral Neuroscience, 2014)
Deep brain stimulation (DBS) of the ventral internal capsule is effective in treating therapy refractory obsessive-compulsive disorder (OCD). Given the close proximity of the stimulation site to the stria terminalis (BNST), we hypothesized that the striking decrease in anxiety symptoms following DBS could be the result of the modulation of contextual anxiety. However, the effect of DBS in this region on contextual anxiety is as of yet unknown. Thus, the current study investigated the effect of DBS on contextual anxiety in an experimental threat of shock paradigm. Eight patients with DBS treatment for severe OCD were tested in a double-blind crossover design with randomly assigned two-week periods of active and sham stimulation. DBS resulted in significant decrease of obsessive-compulsive symptoms, anxiety and depression. However, even though the threat manipulation resulted in a clear context potentiated startle effect, none of the parameters derived from the startle recordings was modulated by the DBS. This suggests that DBS in the ventral internal capsule is effective in treating anxiety symptoms of obsessive-compulsive disorder without modulating the startle circuitry. We hypothesize that the anxiety symptoms present in OCD are likely distinct from the pathological brain circuits in defensive states of other anxiety disorders.